Corrosão e propriedades mecânicas da martensita de nitrogênio formada sobre o aço AISI 409 tratado pelo SHTPN - Berton, Elisiane Maria (2019)
Studies show that pitting is highly dependent on temperature and of the medium, especially the amount of halogen ions such as chloride. Materials intended for these environments are prone to corrosion damage and change in characteristics, reducing its mechanical properties. Surface engineering treatments have been applied to improve mechanical and electrochemical properties in different classes of stainless steels through structural and composition changes of surfaces of materials. In this context, the introduction of nitrogen in solid solution in stainless steels increases the mechanical properties and corrosion resistance. This element reacts in the anodic area, reducing the effect of acidity, besides acting in the reduction of the nitride precipitation tendency and the passive layer stabilization. Among the researches under study is the use of the SHTPN (Solution Heat Treatment after Plasma Nitriding) process, that consists of applying solution treatment to a previously plasma nitrided surface, promoting the dissolution of nitrides and allow the diffusion of nitrogen in the matrix with subsequent formation of a nitrogen-rich layer, in which nitrogen is in solid solution. In this study, it is presented an evaluation of the effects of SHTPN, quenching (1050 ºC) and tempering (at 250, 450 e 650 °C) processes on the nitrogen concentration, microstructure, hardness and corrosion resistance of the nitrided layer, in samples previously treated by SHTPN in the AISI 409 ferritic stainless steel. Corrosion resistance was assessed by means of cyclic potentiodynamic polarization tests carried out in NaCl 0.5 mol/L at different temperatures and with electrolyte medium modification (H2SO4 0.5 mol/L + NaCl 0.2 mol/L), according to ASTM G150. The degree of sensitization was evaluated after tempering by technique of Double Loop Electrochemical Potentiodynamic Reactivation (DL-EPR). Optical and scanning electron microscopy, wavelength dispersive spectroscopy and X-ray diffraction were applied to microstructural and phase characterization. Superficial hardening was evaluated by Vickers microhardness tests and the residual stress values by the hole drilling technique. The results indicate obtention of a high-nitrogen martensitic layer on the surface of the AISI 409 ferritic steel. This layer presented hardness close to 600 HV0.05 with more than 750 µm depth. Results show that quenching of SHTPN samples promoted and extension of the nitrided layer, refinement of the microstructure and improved the homogeneity of the alloy due the better distribution of nitrogen in the layer. Tempering at higher temperatures (450 and 650 °C) showed reduction in corrosion resistance and evidence of intergranular corrosion in the previous austenite grain boundaries, the higher tempering temperatures favored the sensitization due to the formation of Chromium-rich precipitates on grain boundaries. The process with quenching and tempering at 250 ºC led to increasing both hardness as well as pitting and corrosion potentials, even with electrolyte medium or temperature variation. These results confirmed that nitrogen in solid solution increases the surface properties in the AISI 409 stainless steel.